0029 Aberrant Sleep, Spindle, And EEG Power In mGluR5 Knockout Mice. (27th April 2018) - Aguilar, D D; Strecker, R E; Basheer, R; McNally, J M
Abstract: Introduction: The type 5 metabotropic glutamate receptor (mGluR5) is implicated in the etiology of schizophrenia (Sz) as a potential risk gene. Increasing mGluR5 activity may represent a novel therapeutic treatment to rescue NMDA hypofunction associated with this disorder. mGluR5 knockout (KO) mice demonstrate a variety of Sz-like symptoms, including abnormal sleep (Ahnaou et al 2015). Recent clinical work has sparked interest in sleep spindles, 8–15 Hz rhythmic oscillatory events which are decreased in Sz and have been implicated in deficits in cognition and memory. We thus examined sleep/wake and sleep spindle activity of mGluR5 KO mice at baseline and after sleep deprivation (SD). We hypothesized mGluR5 KO mice would demonstrate increased NREM sleep and a Sz-like decrease in sleep spindle density. Methods: Adult male and female wild type C57BL/6 and mGluR5 KO mice (n=6 per group) were used for in vivo frontal EEG/EMG recordings. After 48 hours of tethered habituation, sleep/wake and spindle analysis was performed across a 24 hour control period, and then during SD (6 hours at light onset) and 18 hours recovery sleep. Analysis of EEG power and spindle activity was performed using custom Matlab scripts. Results: mGluR5 KO mice exhibited significantly decreased wake and increased NREM sleep over both light and dark phases. These changes coincide with increased delta power and decreased theta power across all vigilance states. Knockout mice had significantly fewer NREM sleep spindles per minute at the onset of the dark cycle (~17% decrease) and demonstrated a dampening of the circadian rhythm with respect to spindle density and power spectral density. Conclusion: Our data confirm mGluR5 KO mice spend increased time in NREM sleep, replicating previous work. Novel findings include Sz-like abnormalities in sleep spindle density and delta power. Support (If Any): VA CDA IK2BX002130, VA Merit Awards I01BX001356, I01BX002774, I01BX001404, NIMH R01MH39683 & NIMH T32MH016259.